Involvement of epigenetic mechanisms in the development of posttraumatic stress disorder - Tomaž Zupanc (Zdravniški Vestnik, 2012)
Background: Exposure to a traumatic event is required for the diagnosis of posttraumatic stress disorder (PTSM). The relation between psychopathological events, the phenomenology of the trauma, and neurobiological changes related to PTSM is not totally understood. The symptoms of PTSM are believed to reflect stress-induced changes in neurobiological systems representing an inadequate adaptation of neurobiological systems to exposure to severe stressors. Attempts are made to relate different neurobiological changes to the specific features represented in PTSM. It is not clear whether certain neurobiological changes in PTSM reflect preexisting vulnerability or consequences of trauma exposure. It is known that early life environmental events have persistent effects on central nervous tissue structure and function, a phenomenon called ‘developmental programming’. Further, it is known that glucocorticoid hormone mediators may be involved in this process. Recently, epigenetic differences in a neuron-specific glucocorticoid receptor promoter between suicide victims with a history of childhood abuse and those from suicide victims with no childhood abuse were found. It was suggested that changes in glucocorticoid system are mediated by tissue-specific changes in gene expression. Recent studies suggest that epigenetic mechanisms may play an important role in the interplay between stress exposure and genetic vulnerability. Conclusions: Integrating epigenetics into a model that permits prior experience to have a central role in determining individual differences is also consistent with a developmental perspective of PTSD vulnerability.